Peculiar Paramecium Hosts Fail to Establish a Stable Intracellular Relationship With Legionella pneumophila - Watanabe, Kenta; Higuchi, Yusei; Shimmura, Mizuki; Tachibana, Masato; Fujishima, Masahiro; Shimizu, Takashi; Watarai, Masahisa (Frontiers in Microbiology, 2020)
Legionella pneumophila, an intracellular human pathogen, establishes intracellular relationships with several protist hosts, including Paramecium caudatum. L. pneumophila can escape the normal digestion process and establish intracellular relationships in Paramecium. In this study, we identify new Paramecium strains that significantly reduce the number of L. pneumophila during infection. As a result, stable intracellular relationships between L. pneumophila and these Paramecium strains were not observed. These digestion-type Paramecium also showed high efficiency for Escherichia coli elimination compared to other strains of Paramecium. These results suggest that the digestion type strains identified have high non-specific digestion activity. Although we evaluated the maturation process of Legionella-containing vacuoles (LCVs) in the Paramecium strains using LysoTracker, there were no discriminative changes in these LCVs compared to other Paramecium strains. Detailed understanding of the mechanisms of high digestion efficiency in these strains could be applied to water purification technologies and L. pneumophila elimination from environmental water.